Exclusive and Non-Exclusive Breastfeeding among Stunted and Normal 6–9 Month-Old-Children in Jatinangor Subdistrict, Indonesia - Viramitha Kusnandi Rusmil; Tri Oktaviani Prahastuti; Dimas Erlangga Luftimas; Tisnasari Hafsah (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Stunting has become a public health problem in Indonesia, with the prevalence of stunting is 37.2% nationally and 25.6% in West Java. One of the causes of stunting is malnutrition that may occur because of not giving exclusive breastfeeding on the first 1000 days of life (FDL). The purpose of this study was to determine whether there was difference between exclusive and non-exclusive breastfeeding among stunted and normal 6–9 month-old-children. Methods: This study was conducted using a cross-sectional analytic study during August-October 2018 with consecutive sampling method. This study involved 110 pairs of mothers and children aged 6-9 months who resided in villages which were within the work area of Jatinangor Public Health Center. Nutritional status was determined based on length-for-age z score according to WHO. The type of breastfeeding was known based on the questionnaire. Data was analyzed by chi square test. Result: There were 60 of 110 children (54.5%) who did not receive exclusive breastfeeding. The incidence of stunting in children was 12.7% (14 of 110), of whom 10 children had no exclusive breastfeeding (p>0.05).Conclusions: Although the incidence of stunting is higher in non-exclusive breastfeeding group, there is no difference in the proportion of stunting in children aged 6–9 months between those who are exclusively breastfed and those who are not, however, exclusive breastfeeding is encouraged.